Investigation of the Effect of P-Supply on Maize (Zea mays L.) Development - Pokovai, Klára; Kovács, János Géza; Nagy, János (Acta Agraria Debreceniensis, 2020)
Quantification of plant development is important in areas where the actual dates of certain phonological stages should be identified. The influences of different ecological factors are put into algorithms by crop modellers. In this process the effect of plant nutrients are not yet well quantified. This paper gives data on the effect of phosphorus on maize development prior to flowering stage. The main conclusions are as follows: 1. In lack of phosphorus more degree days are needed for flowering then in case of well P-supply. 2. The effect of P is seen not on leaf initialisation (i.e. final eaf number is the same) but rather on the phyllochron interval. 3. P effect on phyllochron interval can be observed at the younger stage (prior to leaf number 10) but not later.